PENGARUH MOTIVASI TERHADAP MINATBERWIRAUSAHA MASYARAKAT DESABAWOLOWALANI LORONG 1 KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - Kristina Halawa (Universitas Nias Raya, 2026)
This research aims to determine the motivation for interest in entrepreneurship in the people of Bawolowalani Lorong 1 Village, Teluk Dalam District, South Nias Regency. The type of research used is quantitative research. The population in this study, the people of Bawolowalani Lorong 1 Village, Teluk Dalam District, was 272 people. The sampling method used was a simple random sampling technique, with a sample size of 73 people. The type of data used is quantitative data and the data source was obtained through distributing questionnaires directly to the people of Bawolowalani Lorong 1 Village. The data collection technique used in this research is the questionnaire technique. The analytical method that will be used to test the hypothesis used in this research is simple linear regression analysis. The results of this research show that motivation influences the entrepreneurial interest of the people of Bawolowalani Lorong 1 Village, Teluk Dalam District, South Nias Regency. The conclusion in this research is that, partially, the motivation variable has a positive and significant effect on interest in entrepreneurship. The suggestion in this research is, in increasing entrepreneurial motivation, people should first have the desire to become entrepreneurs by working hard, developing ideas, thinking optimistically and remaining focused on the goals they want to achieve and to increase interest in entrepreneurship, people need to understand the importance of entrepreneurship, have entrepreneurial skills, daring to take risks and not being afraid of failure, so that interest in entrepreneurship in society will increase.